YIELD AND QUALITY OF WINTER BARLEY GRAIN DEPENDING ON THE CALCULATED RATES OF MINERAL FERTILIZERS APPLIED TO THE PROGRAMMED YIELD ON DARK GREY PODZOLIC SOILS OF THE WESTERN FOREST-STEPPE OF UKRAINE - Parkhuts Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The results of studying the influence of the level of mineral fertilizers on the programmed yield of 5.0, 5.5 and 6.0 c/ha of winter barley of Monro variety on dark gray podzolic soils of the Western Forest-Steppe of Ukraine are presented. The content of mobile forms of nitrogen, phosphorus and potassium in dark gray podzolic soil is as follows: according to Tiurin-Kononova, lightly hydrolyzed nitrogen accoynts for 9.2 mg, mobile phosphorus 10.7 mg and exchangeable potassium according to Chirikov 11.6 mg per 100 g of soil. The following options were included in the scheme of the experiment: control ‒ without fertilizers; recommended norm for this zone N60P60K60 (1.00 : 1.00 : 1.00); the calculated norm of fertilizers N77,7P82,2K79,1 (1.00 : 1.06 : 1.02) for the programmed yield of 5.0 t/ha; calculated norm of fertilizers N95,9P98,5K97,0 (1.00 : 1.03 : 1.01) for the programmed yield of 5.5 t/ha; the calculated norm of fertilizers N114,0P114,7K114,8 (1.00 : 1.01 : 1.01) for the programmed yield of 6.0 t/ha. The following coefficients were used for calculations: coefficient of nutrients utilization from soil ‒ N ‒ 30, P2О5 ‒ 10, K2О ‒ 20; nutrients utilization coefficient from mineral fertilizers ‒ N ‒ 80, P2О5 ‒ 40, K2О ‒ 70. The highest yield of 58.1 c/ha with a programmed yield of 6.0 t/ha, on average over the years of research, was obtained by applying the calculated mineral fertilizers in the norm of N114,0P114,7K114,8. The increase in yield in this variant was 2.85 t/ha, or 96.3 %, and to the recommended norm N60P60K60 ‒ 1.30 t/ha. Provided a yield of 4.51 t/ha, which gave an increase in yield to control 1.55 t/ha, or 52.4 %. The lowest yield of winter barley, i.e. 2.96 t/ha, was in the control variant of the experiment ‒ without fertilizers. The highest protein content of 10.9 % and its total yield of 0.63 t/ha was obtained by making the calculated norm in the variant of N114,0P114,7K114,8 for the programmed yield of 6.0 t/ha. In other variants, the protein content was slightly lower, and in the control it was the lowest and was 9.3 % with a total yield of 0.27 t/ha. By introducing the calculated norm of N114,0P114,7K114,8, the highest net profit of 16498 UAH/ha and the level of profitability of 82,6 % was received